2018
DOI: 10.1016/j.bbmt.2018.01.031
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Post-Transplant Cyclophosphamide Regimen, for Unmanipulated Haploidentical Marrow Transplantation, in Acute Myeloid Leukemia: A Multicenter Study

Abstract: We report a modified post-transplant cyclophosphamide (PT-CY) regimen, for unmanipulated haploidentical marrow transplants, in 150 patients with acute myeloid leukemia (AML). All patients received a myeloablative regimen, cyclosporine A (CsA) on day 0, mycophenolate on day +1, and PT-CY 50 mg/kg on days +3 and +5. The median age was 51 (range, 17-74) years, 51 (34%) patients had active disease at transplant, and the median follow-up of surviving patients 903 (range, 150-1955) days. The cumulative incidence (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…We speculated that the double doses of 50 mg/kg of PT/Cy could increase the Tregs‐to‐Tcon ratio by more effectively eradicating alloreactive T cells. Indeed, the incidence of acute GVHD was high compared to that in patients receiving the original dose of PT/Cy . Nevertheless, the incidence of chronic GVHD was very low, suggesting that the two doses of 25 mg/kg PT/Cy were sufficient to regulate chronic GVHD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We speculated that the double doses of 50 mg/kg of PT/Cy could increase the Tregs‐to‐Tcon ratio by more effectively eradicating alloreactive T cells. Indeed, the incidence of acute GVHD was high compared to that in patients receiving the original dose of PT/Cy . Nevertheless, the incidence of chronic GVHD was very low, suggesting that the two doses of 25 mg/kg PT/Cy were sufficient to regulate chronic GVHD.…”
Section: Discussionmentioning
confidence: 98%
“…Many prospective studies of PT/Cy‐haplo have demonstrated its safety profile and efficacy, irrespective of whether the type of graft used was bone marrow (BM) or peripheral blood (PB) . The use of PT/Cy‐haplo has become widespread globally, and it is becoming a platform technique for unmanipulated HLA‐haploidentical hematopoietic cell transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to this data, the European Registry Study defi ned recipient age, use of PBSC and combination prophylaxis as the risk factors [20]. Th e diff erences might be due to diff erent PTCy schedule (day +3, +5), use of cyclosporine instead of tacrolimus, duration of immunosuppression [29]. Th e absence of diff erences between PBSC and BM is explained by single-agent PTCy prophylaxis in the matched bone marrow group and combination with tacrolimus and MMF in the PBSC group, which alleviated the diff erences.…”
Section: Discussionmentioning
confidence: 92%
“…Owing to the success of cyclophosphamide after transplantation tolerance in the setting of haplo-HCT, this regime has been extended to the patients who underwent allogeneic HSCT from HLA-matched donors. Acute GvHD is a challenge that must be managed, and its incidence can be reduced using the utility of one or more immunosuppressive agents 21 . In this perspective, we recommend the use of cyclophosphamide and cyclosporine as prophylactic agents for GvHD.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Chiusolo et al . suggested that post-transplant cyclophosphamide regimen provided protection against GVHD, low toxicity, and encouraging low relapse incidence in AML patients who received unmanipulated haploidentical marrow transplants along with a myeloablative regimen 21 . Bacigalupo et al .…”
Section: Discussionmentioning
confidence: 99%